2020
DOI: 10.7759/cureus.6734
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Variational Anatomy of the Medial Circumflex Femoral Artery: A Case Report of a Post-catheterization Femoral Arteriovenous Fistula

Abstract: The medial circumflex femoral artery (MCFA) typically presents as a major branch of the profunda femoris artery or it can also directly originate from the common femoral artery. Many anatomical variations of the MCFA have been described due to their clinical significance. We herein report a case of an unusual anatomical variation of the MCFA crossing anterior to the femoral vein that led to iatrogenic arteriovenous fistula formation after cardiac catheterization. The identification of such rare vascular anatom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…In the current literature, several authors have mentioned the anatomical variant origin and pathway of the PCHA. 3,5,6,[12][13][14][15][16][17][18] In a study of 83 cadavers conducted by Olinger and Benninger, 15 the origin of the PCHA was observed from four different sources: the axillary artery, the subscapular artery, the deep brachial artery, and the lateral thoracic artery. These authors reported that the PCHA originated from the axillary artery in 77.1% of specimens, from the subscapular artery in 12%, and separated from the deep brachial artery in 8.4% of specimens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current literature, several authors have mentioned the anatomical variant origin and pathway of the PCHA. 3,5,6,[12][13][14][15][16][17][18] In a study of 83 cadavers conducted by Olinger and Benninger, 15 the origin of the PCHA was observed from four different sources: the axillary artery, the subscapular artery, the deep brachial artery, and the lateral thoracic artery. These authors reported that the PCHA originated from the axillary artery in 77.1% of specimens, from the subscapular artery in 12%, and separated from the deep brachial artery in 8.4% of specimens.…”
Section: Discussionmentioning
confidence: 99%
“…However, only a few studies have reported detailed statistics related to the origin, length, diameter, pathways, and branches. 1,3,5,6,[10][11][12][13][14][15][16][17][18] According to the classical description, the vascular pedicle of the deltoid free flap is separated from the PCHA system. 1,6,10 Although several authors have reported the diameter of this artery, there are significant discrepancies in their findings.…”
mentioning
confidence: 99%